Akurasi otoskopi video digital dalam mendiagnosis otitis media akut pada pasien pediatri: sebuah tinjauan sistematik - Anak Agung Wira Ryantama; Ni Luh Parameswari Praptika; Ni Nyoman Astrid Tri Bhuwana (Intisari Sains Medis, 2022)
Introduction: Acute otitis media one of the most prevalent ear and throat infection, mostly affecting children. Diagnosis of this condition was complicated by the perceived invasive procedure and the shortage of qualified otologist. Digital video otoscopy is a new and evolving concept in otology which could be further enhanced with telemedicine. It increases access to specialist otologist care by having the examination performed by less qualified healthcare professional. In this review we would like to assess the newest evidence on digital video otoscopy as diagnostic modality for acute otitis media.Methods: We identified literature published from 2000 to 2020 from MEDLINE and Google Scholar. We included studies which reported diagnosis of acute otitis media using digital video otoscopy devices. We include both descriptive and analytical studies. We exclude literatures that reported secondary results or those that does not have acute otitis media as the diagnosis of interest. Articles that fulfill the criteria was then analyzed qualitatively to identify the themes that emerges.Results: Literature search resulted in 10 included studies which includes descriptive studies, diagnostic studies, and RCTs. Digital video devices used varied from add-ons to smartphones to dedicated digital video otoscopy results. The reported examiners also varied from otologist, general practitioners, to telemedicine facilitators. Most studies concur that digital video otoscopy provided adequate inter-examiner and intra-examiner reliability. At the same time, digital video otoscopy provides adequately accurate diagnosis of acute otitis media. Where comparison was available, the accuracy of digital video otoscopy was not significantly different compared to other modes of otoscopy.Conclusions: Digital video otoscopy provide adequately reliable and accurate diagnostic examination for acute otitis media. Some digital video otoscopy system was simple enough to be operated by nurses or telemedicine facilitators, supporting the utilization of this system for telemedicine.